CASE REPORTA 42-year-old patient with alcoholic cardiomyopathy - Irzmański, Robert; Serwa-Stępień, Ewa; Barylski, Marcin; Banach, Maciej; Rysz, Jacek; Kowalski, Jan; Pawlicki, Lucjan (Archives of Medical Science, 2005)
Introduction: Alcoholic cardiomyopathy represents about 3.8% of all cardiomyopathy cases and it is a result of long-term (>5 years) alcohol consumption (>90 g of alcohol per day). It occurs twice as frequently in men as in women. Case report: We present the case of a 42-year-old patient, not treated for chronic diseases so far, with positive incriminating familiar anamnesis for ischemic heart disease, who was hospitalized in our Department because of progressive reduction of effort tolerance for 2 weeks with squeezing in the chest and dyspnea (\"asthma cardiale\" type). Basing on the clinical course, anamnesis from family members and additional tests performed, alcoholic cardiomyopathy was diagnosed. Conclusions: Alcoholism is one of the main causes of myocardial damage. Treatment of patients with alcoholic cardiomyopathy should include alcohol abstinence and recommended heart failure pharmacotherapy.